Time-Resolved Particulate Emissions Monitoring of Cookstove Biomass Combustion Using a Tapered Element Oscillating Microbalance. Issue 6 (3rd June 2017) - Sullivan, Benjamin; Allawatt, Garrett; Emery, Ashley; Means, Paul; Kramlich, John; Posner, Jonathan
ABSTRACT: In this work, a tapered element oscillating microbalance (TEOM) system is developed to measure time-resolved cookstove particulate matter (PM) emissions less than 2.5 µm in diameter. The TEOM system requires modifications and calibration for cookstove applications to provide results consistent with the standard gravimetric filter method. We obtained a TEOM calibration constant of 0.67 for cookstove emissions. The TEOM system enables the correlation of operator actions and operating conditions with transient particulate emission events. We show that PM produced during refueling and lighting phases can significantly contribute to total particulate emissions over a cookstove comparison test, especially for cleaner stoves.